Tinjauan Kriminologis Terhadap Faktor-Faktor Penyebab Terjadinya Tindak Pidana Dibidang Perikanan Dan Penanggulangannya Di Laut Kabupaten Bintan - Alhadi, Hafiz dwi; Nelwitis; Kurniawan, Iwan (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2023)
Fishery resources are one of the many natural resources in Indonesia. Its vast aquatic territory makes Indonesia an archipelagic country that hosts numerous activities at sea. The abundance of activities utilizing marine fisheries resources has led to actions detrimental to society. This research examines several issues, including: 1) What factors lead to criminal activities in the field of marine fisheries in the waters of Bintan Regency; and 2) What efforts are made by law enforcement authorities to prevent and address criminal activities in the field of marine fisheries in Bintan Regency. The research method used is empirical juridical research. Data collection is conducted through interviews with relevant parties and literature research related to the research topic. The obtained data is analyzed qualitatively and presented descriptively. The research results indicate that Bintan Regency is vulnerable to fisheries-related crimes. Several cases have been handled by the relevant authorities. The factors causing fisheries-related crimes in Bintan Regency can be summarized as follows: first, low awareness, compliance, and legal effectiveness; second, low economic status among fishermen; and third, low educational levels. Efforts made by law enforcement authorities include preventive measures such as legal counseling, patrols, redirecting community activities, providing environmentally friendly modern assistance, and establishing community monitoring groups. In addition, repressive efforts are also carried out through strict law enforcement, including arrests and examinations that result in the application of sanctions in accordance with the laws of Indonesia